Integration and interpersonal relationships of moroccan immigrant students of compulsory secondary education in Andalusia Spain - Llorent-Bedmar, Vicente; Llorent-Vaquero, Mercedes (Papeles de Población, 2017)
The current Spanish society is characterized for an a abundance of immigrants and recently for an emerging migration. The importance of the Moroccan community in Andalusia (Spain) encourages us to contribute for their better integration. It is interesting to know the degree of integration in society and interpersonal relationships. We have used a qualitative methodology with quantitative data, carrying out a stratified sampling to study Moroccan students of ESO. Their life has changed significantly in Spain. However, we estimate important to maintaining their customs and traditions, but we are immersed in a constant process of assimilation of cultural and social norms for the host society. The most common problems are the culture collision, language difficulties, family-school relationships and school segregation.